2017
DOI: 10.3390/v9080215
|View full text |Cite
|
Sign up to set email alerts
|

Poxviruses Utilize Multiple Strategies to Inhibit Apoptosis

Abstract: Cells have multiple means to induce apoptosis in response to viral infection. Poxviruses must prevent activation of cellular apoptosis to ensure successful replication. These viruses devote a substantial portion of their genome to immune evasion. Many of these immune evasion products expressed during infection antagonize cellular apoptotic pathways. Poxvirus products target multiple points in both the extrinsic and intrinsic apoptotic pathways, thereby mitigating apoptosis during infection. Interestingly, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 294 publications
(497 reference statements)
2
28
0
Order By: Relevance
“…Our results are consistent with the enhanced tumor selectivity of a VACV Western Reserve strain harboring a double deletion of two anti-apoptosis genes (SPI-1 and SPI-2) 31 . Other VACV strains encode other virulence factors with anti-apoptotic activity 32 . Future investigations should examine the potential of deleting additional anti-apoptotic factors to improve poxvirus vectors as OVs.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are consistent with the enhanced tumor selectivity of a VACV Western Reserve strain harboring a double deletion of two anti-apoptosis genes (SPI-1 and SPI-2) 31 . Other VACV strains encode other virulence factors with anti-apoptotic activity 32 . Future investigations should examine the potential of deleting additional anti-apoptotic factors to improve poxvirus vectors as OVs.…”
Section: Discussionsupporting
confidence: 83%
“…Another class of interesting targets are the viral genes involved in cell death [42, 43]. Previously, we showed that deletion of the Spi-2/Spi-1 genes from VV renders it highly-attenuated in normal tissue, yet it retains replication competence in cancer cells and functions as a potent oncolytic VV [44].…”
Section: Biology Of Vaccinia Virusmentioning
confidence: 99%
“…DNA viruses typically encode prosurvival factors in their genome. For example, poxvi- ruses express serpins, which inhibit the activity of cellular caspases (41). Cytomegaloviruses utilize virally encoded inhibitors of Bax and Bak, which trigger the intrinsic apoptotic pathway, for preventing cell death (42).…”
mentioning
confidence: 99%